Page from "Het Leven" with scenes from the murder on the English marshall Wilson (top, left) at Eaton Place in London by two Irish revolutionaries (middle). Text on the front
Page from "Het Leven" with scenes from the murder on the English marshall Wilson (top, left) at Eaton Place in London by two Irish revolutionaries (middle). Text on the front.